Free at last! : the story of Martin Luther King, Jr. - Bull, Angela (London : Dorling Kindersley, 2000)
A biography of the civil rights leader, covering his childhood, leadership, powerful speeches, assassination, and greatest influences.
Includes index.
Keywords: African Americans -- Biography; African Americans -- Biography -- Juvenile literature; African Americans -- Civil rights -- History -- 20th century -- Juvenile literature; Baptists -- United States -- Clergy -- Biography -- Juvenile literature; Civil rights movements -- History; Civil rights workers; Civil rights workers -- United States -- Biography -- Juvenile literature; Clergy; King, Martin Luther, Jr., 1929-1968.; King, Martin Luther, Jr., 1929-1968 -- Juvenile literature